2019
DOI: 10.1093/cid/ciz639
|View full text |Cite
|
Sign up to set email alerts
|

Pre-existing Antineuraminidase Antibodies Are Associated With Shortened Duration of Influenza A(H1N1)pdm Virus Shedding and Illness in Naturally Infected Adults

Abstract: Background Influenza causes a substantial burden worldwide, and current seasonal influenza vaccine has suboptimal effectiveness. To develop better, more broadly protective vaccines, a more thorough understanding is needed of how antibodies that target the influenza virus surface antigens, hemagglutinin (HA) (including head and stalk regions) and neuraminidase (NA), impact influenza illness and virus transmission. Methods We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 28 publications
0
55
0
Order By: Relevance
“…However, less attention is paid to the antigenicity of the NA, and it is not known if human anti-NA antibodies arising from novel Yamagata strains broadly cross-react with older viruses. Increasing awareness of the importance of influenza virus NA immunity has prompted recent efforts to understand the protective effect of anti-NA immunity in animal models; studies have shown that the anti-NA antibodies can significantly reduce virus titers and shedding of influenza B viruses (27) and lower the duration of illness in influenza A/H1N1 virus (28). Crucially, anti-NA antibodies can broadly cross-react against H1N1 and H3N2 subtype viruses, but current influenza vaccines cannot induce an efficient NA response (29).…”
Section: Discussionmentioning
confidence: 99%
“…However, less attention is paid to the antigenicity of the NA, and it is not known if human anti-NA antibodies arising from novel Yamagata strains broadly cross-react with older viruses. Increasing awareness of the importance of influenza virus NA immunity has prompted recent efforts to understand the protective effect of anti-NA immunity in animal models; studies have shown that the anti-NA antibodies can significantly reduce virus titers and shedding of influenza B viruses (27) and lower the duration of illness in influenza A/H1N1 virus (28). Crucially, anti-NA antibodies can broadly cross-react against H1N1 and H3N2 subtype viruses, but current influenza vaccines cannot induce an efficient NA response (29).…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Anti-NA enzyme-linked immunosorbent assays (ELISAs), which do not suffer from this shortcoming, have recently been used to show a negative correlation between anti-NA titers and virus shedding in humans in a cohort study. 24 In the same cohort, anti-HA stalk antibodies have been shown to be an independent correlate of protection against both infection as well as symptomatic disease. 14 Cross reactive CD4+ and CD8+ cells have also been identified as correlates of protection in human challenge and cohort studies.…”
Section: E Xis Ting and Novel Correl Ate S Of Protec Ti Onmentioning
confidence: 93%
“…Of note, anti‐HA stalk antibodies can interfere with H6NX‐based NI assays which have to be taken into account in their interpretation . Anti‐NA enzyme‐linked immunosorbent assays (ELISAs), which do not suffer from this shortcoming, have recently been used to show a negative correlation between anti‐NA titers and virus shedding in humans in a cohort study . In the same cohort, anti‐HA stalk antibodies have been shown to be an independent correlate of protection against both infection as well as symptomatic disease .…”
Section: Existing and Novel Correlates Of Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, NA antibodies have been shown to be protective in both chickens and humans (Murphy et al, 1972;Clements et al, 1986;Webster et al, 1988). In humans, antibodies against NA have been associated with decreased viral shedding and shortened duration of symptoms (Maier et al, 2019). Recent studies have highlighted the importance of examining neuraminidase inhibition titers as well as hemagglutinin inhibition titers as a measure of influenza disease severity, suggesting that NA-based protection should be an important consideration when developing new influenza vaccines (Monto et al, 2015;Memoli et al, 2016).…”
Section: Neuraminidase-directedmentioning
confidence: 99%